Moving civilians to the front of patrol cars: Built space, embodiment, and social control during police encounters - Buscariolli, André (Journal of pragmatics, 2023)
This article uses recordings of on-the-street police encounters to analyze how officers move civilians to the front of patrol cars and request them to sit on the bumper or put their hands on the hood. These spatial maneuvers entail a suspension of civilians' movement rights, establishing their identity as legally detained subjects. Thus, though seemingly mundane, by moving civilians to the front of the car, officers exercise social control in its most elementary form: practical tasks comprising methodic police work. Dashcam recordings in English were obtained from the police department of an American West Coast city and analyzed using conversation analysis. Findings demonstrate that having civilians sit on the bumper or put their hands on the hood imposes asymmetric participation frameworks whereby officers maximize their control over their subjects' bodies while restricting the latter's access to them. Such asymmetry is adapted to (a) tasks officers undertake to workout out an outcome for the encounter and (b) situational contingencies associated with possible threat. Importantly, officers accomplish such spatial formations – and, thereby, civilians' status as detained subjects – moment-by-moment, continuously monitoring their subjects' bodies for compliance and incrementing their actions as trouble emerges.